2016
DOI: 10.1002/jhm.2611
|View full text |Cite
|
Sign up to set email alerts
|

The risk‐outcome‐experience triad: Mortality risk and the hospital consumer assessment of healthcare providers and systems survey

Abstract: BACKGROUND Studies have shown an association between the Hospital Consumer Assessment of Healthcare Providers and Systems Survey (HCAHPS) scores and clinical quality. The mortality risk on admission predicts adverse events. It is not known if this risk also portends a suboptimal patient experience. OBJECTIVE To determine if the admission mortality risk identifies an experience of care risk. DESIGN A retrospectively assembled cohort in which individual HCAHPS survey responses were linked to the admission risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Patients included in the MEPS database were also not tracked longitudinally over time. Additionally, the MEPS database contains limited variables and some variables that might have had an impact on patient satisfaction and outcomes, such as patient comorbidities contributing to mortality risk, were not included (8). Data were also exclusively derived from patients in the United States who were noninstitutionalized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients included in the MEPS database were also not tracked longitudinally over time. Additionally, the MEPS database contains limited variables and some variables that might have had an impact on patient satisfaction and outcomes, such as patient comorbidities contributing to mortality risk, were not included (8). Data were also exclusively derived from patients in the United States who were noninstitutionalized.…”
Section: Discussionmentioning
confidence: 99%
“…Kaye et al noted a possible relationship between high patient satisfaction and improved outcomes in some patient populations (7). In a separate study, Cowen et al suggested a potential interrelationship between patient mortality risk and patient satisfaction and outcomes (8). However, few studies have specifically examined the association of self-reported patient satisfaction scores with a broad range of health outcome metrics.…”
Section: Introductionmentioning
confidence: 99%
“…Third, we were unable to adjust for some patient characteristics, including illness severity and depression, which are associated with lower patient-satisfaction scores [28, 29]. However, we adjusted for other Elixhauser co-morbidities and the Hospital Compare HCAHPS measure includes an adjustment for self-rated health.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the Journal of Hospital Medicine, Cowen and coauthors shed light on the experience of inpatients on medical and surgical services with a high risk of mortality on admission, as measured by Hospital Consumer Assessment of Healthcare Providers and Systems Surveys (HCAHPS). 1 In their study population, even after adjustment for some confounders, these patients tended to rate responsiveness of hospital staff and communication by doctors lower than patients with a low risk of mortality on admission.…”
mentioning
confidence: 85%